Clozapine Induced Pityriasiform Eruption - Bhatia M S; Choudhary Sandeep; Khanna Sanjay; Agrawal Pradeep (Wolters Kluwer Medknow Publications, 1997)
Clozapine is a new atypical antipsychotic drug. Pityriasiform eruption induced by clozapine is described for the first time.